Forced labour and rural resistance in the tobacco farms in Nampula Province: a history of rural change in Mozambique, 1961-1975 - Navohola, Ernesto Augusto (My University, 2012)
This study focuses on forced labour and rural resistance in the tobacco producing farms in Nampula Province during the period 1961-1975. Key changes in the period include the introduction of new incentives to produce raw materials for the economy of the metropolis (Portugal); the abolition of the Regulation of Native Labour established in the 19th century; the institution of a new law of rural work to guarantee the co-operation of the African labour force; the construction of settlements and a new salary scale to guarantee the wages of the workers. The adoption of new methods of recruitment of workers and the introduction of forced marriages and unpaid child labour by the Roman Catholic Mission of Nampula are also important factors. The study outlines tobacco production in Nampula, from its beginning until the year of 1960. This theme is explored in the wider context of the colonial experience in Northern Mozambique. The thesis suggests that the production of tobacco was done in a discriminatory manner. White settlers took the forefront of tobacco production and peasants were not allowed to grow tobacco. Although the change of 1960s allowed for a few blacks producers the majority of the Makua population continued working as forced labourers on settlers’ farms. This study explores the impact of the system on men, women, youths and children in rural Makua, and their relationship with the colonisers. It also demonstrates the way the colonizers sought to organize work and how Africans practised forms of resistance as part of their response to colonial exploitation.
M.A. Faculty of Humanities, University of the Witwatersrand, 2011